2021
DOI: 10.1002/ddr.21869
|View full text |Cite
|
Sign up to set email alerts
|

Propofol promotes migration, alleviates inflammation, and apoptosis of lipopolysaccharide‐induced human pulmonary microvascular endothelial cells by activating PI3K/AKT signaling pathway via upregulating APOM expression

Abstract: Propofol (PRO), a clinical potent intravenous anesthetic, plays a significant role in relieving inflammatory diseases by repressing the release of inflammatory cytokines. The present study was aimed to reveal a novel mechanism by which PRO alleviates acute lung injury (ALI). Lipopolysaccharide (LPS) was utilized to induce human pulmonary microvascular endothelial cells (HPMECs) so as to simulate the microenvironment of ALI, and the expression of apolipoprotein M (APOM) was examined with western blotting. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In a previous study by the authors, KEGG pathway enrichment analysis revealed that the PI3K/AKT signalling pathway was the main signalling pathway for gene enrichment in lung tissues after PQ poisoning and AH 2 QdS treatment (26). The PI3K/AKT signalling pathway is important in the regulation of cell survival as well as repairing endothelial damage (43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study by the authors, KEGG pathway enrichment analysis revealed that the PI3K/AKT signalling pathway was the main signalling pathway for gene enrichment in lung tissues after PQ poisoning and AH 2 QdS treatment (26). The PI3K/AKT signalling pathway is important in the regulation of cell survival as well as repairing endothelial damage (43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt signaling pathway can promote cell survival and growth in several ways, including the suppression of inflammation and the regulation of apoptosis and ERS. 27 For example, PI3K/Akt downregulates pro-apoptotic proteins including Bad, BAX, and caspase. 28 The regulation of apoptosis to protect against lung injury is also mediated by the activation of PI3K/Akt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, SREBF1, as the central transcription factor regulating lipid metabolism, mainly regulates the expression of the factors required for fatty acid synthesis ( 30 ), which has recently been proved to be the reason why PI3K-AKT-mTOR signaling pathway endows cancer cells with the ability to resist iron death ( 31 ). Furthermore, ApoM is closely related to the AKT-mTOR signaling pathway and is associated with inflammation, apoptosis and insulin resistance ( 11 , 32 , 33 ). Future work will aim to prove that ApoM affects SREBF1 through certain pathways (at least the PI3K-AKT-mTOR signaling pathway).…”
Section: Discussionmentioning
confidence: 99%